Implementation of Type-2 Fuzzy Logic Controller in PMSM Drives Using DSP - Said Wahsh; Y. Ahmed; Abo Elzahab (Institute of Advanced Engineering and Science, 2018)
This paper presents interval type-2 fuzzy logic (IT2FL) controller applied on a direct torque controlled (DTC) permanent magnet synchronous motor (PMSM), using digital signal processing (DSP). The simulation of PMSM with space vector pulse widths modulation (SVPWM) inverter presented under several operating condition. To verify the simulation results a hard ware setup is prepared and tested at several operating conditions using dspace 1102 DSP model. The experimental and simulation results are in agreement and the torque dynamic response is very rapid and the system achieves the steady state in a very short time.